Ahlul Haq Wassunnah dalam Matan HPT Muhammadiyah Bagian Ketuhanan Perspektif Wahyudi Sarju Abdurrahim - Dwi Jaka Anandika; Mahmud Muhsinin; Muhammad Maulana Mas'udi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2022)
This article concentrates on the Arabic language editor written in the Muhammadiyah's Divinity Section of the Tarjih Judgment Association (HPT). Even though it is in the form of writing with a short editorial, it contains clues for findong references used by tarjih muhammadiyah scholars in the early period of its formulation. The purpose of this study is to examine the thoughts of Wahyudi Sarju Abdurrahim regarding his views on the Muhammadiyah creed which is implied in the HPT book. The term Ahlul Haq Wassunnah contained in the text of the HPT chapter on Faith is used as an entry point in tracking the literacy sources of the tarjih scholars in formulating the HPT of Muhammadiyah. Furthermore, he compared the classical books (turast) in the field of kalam science from various schools of faith with the HPT Muhammadiyah to find the suitability of the texts and its meanings. Of the many schools of creed, finally converging on two great figures, namely Abu Hasan Al-Asy'ari and Muhammad bin Abdul Wahab. The reason for choosing these two figures was because they were seen as representing the two currents of kalam thought that developed in Muhammadiyah. The type of research used in this article is library research with primary sources matan (editors) of HPT Muhammadiyah and secondary sources in the form of classic books (turats) by Mutakallimin scholars from the early era of their appearance to the late era.